ENGLISH LANGUAGE EDUCATION IN TIMES OF CHANGE : A PRELIMINARY SURVEY OF SOUTHEAST ASIAN UNIVERSITIES - Collin, Jerome; Kriangkrai, Vathanalaohoa; Patcharin, Kangkha; Boonyarit, Omanee; Mei Ph’ng, Lee; Esther John, Perry; Ting, Su Hie (ACADEMIA INDUSTRY NETWORKS, 2022)
English language education (ELE) has been extensively studied in various contexts and from various perspectives including histories, curricula, policies, and practices. However, in recent years there has been an increasing body of work examining ELE in times of dramatic socio-economic change. The study presented in this paper aimed to add to this body of work by investigating the implementation of ELE in Southeast Asian universities during these periods of transformation. The study specifically investigated the major events that took place during such periods and how these events affected ELE, particularly English language teaching and learning practices within the respective universities. A survey with 47 English language educators from selected Southeast Asian universities revealed that COVID-19 was one of the major events that affected their ELE. A majority of the participants reported having similar experiences with such events and resorting to various common methods in their English language lessons. Such similarities are important as they help rethink the usual way ELE in the era of change has been discussed. More importantly, these similarities call attention to look beyond the differences to find commonalities in the implementation of ELE in times of change, which may open up much-needed conversations about how to support and strengthen the teaching and learning of English in today’s ever-changing and challenging world.